Museum der Bildenden Künste Leipzig - Jahresheft 2001. - Bühler, Hans-Peter; Bühler, Marion; Dittmer, Jörg; Klugmann, Claudia; Lazarus, Anka-Roberta; Mehnert, Karl-Heinz; Nicolaisen, Jan; Porstmann, Gisbert; Sander, Dietulf; Schmidt, Hans-Werner; Stoschek, Jeannette; Museum der bildenden Künste, Leipzig (Leipzig : Museum der bildenden Künste, 2002)
Baumgärtel, Tilo ; Ebersbach, Wolfram ; Havekost, Eberhard ; Klinger, Max ; Balkenhol, Stephan ; Heisig, Bernhard ; Huber, Stephan ; Muller, Richard ; Ranft, Thomas ; Hoch, Matthias ; Klotz, Siegfried ; Kowski, Uwe ; Krug, Karl ; Ackermann, Franz ; Goltzsche, Dieter ; Kraut, Alexander Johannes ; Richter, Daniel ; Schad, Christian ; Schmitt, Hermann Valentin ; Wols ; Kluge, Gustav ; Lausen, Uwe ; Nicolai, Olaf ; Oelze, Richard ; Altenbourg, Gerhard ; Scheibitz, Thomas ; Gaul, August ; Mataré, Ewald ; Grcic, Tamara
Duits
boek